2024
DOI: 10.1001/jamanetworkopen.2023.54751
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Status and Survival in Patients With Early-Stage Primary Cutaneous Melanoma

Katherine M. Jackson,
Peter C. Jones,
Laura M. Fluke
et al.

Abstract: ImportanceWhile smoking is associated with a decreased incidence of cutaneous melanoma, the association of smoking with melanoma progression and death is not well defined.ObjectiveTo determine the association of smoking with survival in patients with early-stage primary cutaneous melanoma.Design, Setting, and ParticipantsThis cohort study performed a post hoc analysis of data derived from the randomized, multinational first and second Multicenter Selective Lymphadenectomy Trials (MSLT-I and MSLT-II). Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…Reported relationships between smoking and melanoma are inconsistent, with some reports demonstrating a paradoxical decreased risk of melanoma in smokers [33][34][35]. Despite this, a cohort study of 6279 patients with stage 1 or stage 2 melanoma reported a greater risk of melanomaassociated death in current smokers (HR = 1.5) [36]. A meta-analysis including 1326 cases of renal cell cancer (RCC) from cohort studies and 6032 cases of RCC from case-control studies reported a relative risk of 1.4 for the development of RCC in ever-smokers [37].…”
Section: Discussionmentioning
confidence: 99%
“…Reported relationships between smoking and melanoma are inconsistent, with some reports demonstrating a paradoxical decreased risk of melanoma in smokers [33][34][35]. Despite this, a cohort study of 6279 patients with stage 1 or stage 2 melanoma reported a greater risk of melanomaassociated death in current smokers (HR = 1.5) [36]. A meta-analysis including 1326 cases of renal cell cancer (RCC) from cohort studies and 6032 cases of RCC from case-control studies reported a relative risk of 1.4 for the development of RCC in ever-smokers [37].…”
Section: Discussionmentioning
confidence: 99%